The Role of Carbon Accountant in Corporate Carbon Management Systems: A Holistic Approach - Francis Chinedu Egbunike; Ochuko Benedict Emudainohwo (Universitas Pasundan, 2017)
Carbon accounting consists of a combination of advanced cost allocation techniques such as activity-based management and life-cycle costing; that improve the identification and assignments of carbon-related expenses and overheads to such objects as products, services, customers and organizational processes. The study therefore sets out to find the role of carbon accountant in corporate management systems. Data used for this investigation were collected from primary and secondary sources. Primary data are first-hand information from respondents while Secondary data include textbook, Annual Reports and financial statements and internet facilities. The study employed descriptive survey and ex-post facto research design and the formulated hypotheses were tested by use of T-Test and OLS Regression. Based on the analysis and the hypothesis tested, it showed that there is a statistically significant relationship between carbon accounting and corporate performance of selected quoted Manufacturing Companies and based on this findings, it was recommended amongst others that, adaptation to conditions that include long-term changing dynamics of the natural environment should be encouraged and the focus of finance and accounting system should not only cover short-term outcomes and management of short-term costing, reporting and disclosure but also long-term climate risks.